2020
DOI: 10.1177/0891243220914521
|View full text |Cite
|
Sign up to set email alerts
|

The Failure of Gender Equality Initiatives in Academia: Exploring Defensive Institutional Work in Flemish Universities

Abstract: Although a large number of studies have explored the main causes of gender inequality in academia, less attention has been given to the processes underlying the failure of gender equality initiatives to enhance gender representation, especially at the professorial level. We offer a critical discourse analysis of recently promulgated gender policy documents of the five Flemish universities, and demonstrate that defensive institutional work is a fundamental process underlying resistance to gender equality in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 58 publications
0
36
0
Order By: Relevance
“…We are waking before dawn, and/or working late into the night, on the weekends—whatever we can do to find the time and space needed for the deep thinking required by our profession. It seems that rather than resisting the sexist structures and assumptions of our institutions (Roos, Mampaey, Huisman, & Luyckx, 2020; Savigny, 2014), we are resisting the challenge that the COVID‐19 pandemic policy structure has posed for women (and in our cases, mothering women) in academia, and perhaps most worryingly, we may have better luck fighting this virus than we do fighting the cultures of academic institutions.…”
Section: Blending Blurring and Colliding Spheres: Role Conflictmentioning
confidence: 99%
See 1 more Smart Citation
“…We are waking before dawn, and/or working late into the night, on the weekends—whatever we can do to find the time and space needed for the deep thinking required by our profession. It seems that rather than resisting the sexist structures and assumptions of our institutions (Roos, Mampaey, Huisman, & Luyckx, 2020; Savigny, 2014), we are resisting the challenge that the COVID‐19 pandemic policy structure has posed for women (and in our cases, mothering women) in academia, and perhaps most worryingly, we may have better luck fighting this virus than we do fighting the cultures of academic institutions.…”
Section: Blending Blurring and Colliding Spheres: Role Conflictmentioning
confidence: 99%
“…The rigid academic structure and gender bias common in the academic industry (Caretta et al, 2018; Roos et al, 2020; Savigny, 2014) was viewed as having the potential to position women at a more significant disadvantage unless they had options to work at an equivalent employment ratio to men. We all identified the need to recognize the significant burden of fitting full‐time academic work around family, which may deserve more attention in academic career performance weightings:
I am a full‐time worker, have been both before and after [x] was born since I went back to paid work after taking minimal maternity leave … Not just for financial reasons, but also because the impact on my career would have been even more pronounced.
…”
Section: Fears and Hopesmentioning
confidence: 99%
“…The erroneously assumed meritocracy and gender blindness in recruitment and selection processes are part of the discursive resistance to the entry of women to all boards (e.g. Roos andZanoni 2018, Hovden et al 2019), but this resistance may be especially salient to sport as a field. The regime of truth (Foucault 1972) constructed in sport about gender may make resistance to the entry of women board members in the form of defensive institutional work more acceptable in sport governance than in other fields.…”
Section: Defensive Institutional Work In Sport Governancementioning
confidence: 99%
“…Although the previously cited literature describes various factors that may be addressed in policy efforts to increase gender balance on boards of directors, relatively few scholars have looked specifically at why these attempts to create change may fail and how insiders of organisations that purport to value diversity, such as members of the board of governance, may discursively resist measures that might increase gender equity. In one of the few existing studies, Roos and colleagues (Roos andZanoni 2018, Roos et al 2020) found that directors drew on discursive resources to legitimate the status quo and to resist the institutionalisation of measures that could increase the number of women on boards of governance. Roos et al (2020) have called the use of a combination of discourses by powerful organisational actors to resist change in the underrepresentation of women in positions of leadership, 'defensive institutional work'.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation